Environmental Kuznets Curve, biodiversity and sustainability - Renate Schubert; Simon Dietz (University of Bonn, Center for Development Research (ZEF), 2001)
This paper deals with the question of whether for biodiversity an Environmental Kuznets Curve (EKC) exists. In addition, we are interested in identifying the key determinants of the falling limb of such a curve. An Environmental Kuznets Curve here is understood to be a graphical representation of a function with the amount of environmental damages in a country as the dependent variable and with per capita income as the independent variable. The graph of this function is assumed to have the shape of an inverted U. As with the general case of environmental damages, the existence of an EKC for biodiversity cannot be proven empirically. On the contrary, an EKC for biodiversity seems rather not to exist. Given the rapid rate of depletion of species diversity, policy measures to protect or even increase the number of species play an important role. In particular, property rights regimes seem to matter with respect to the biodiversity issue. Doubts over the existence of an EKC for biodiversity cast doubts over the corresponding sustainability implications. However, it seems reasonable to interpret losses in species numbers as a signal of danger for sustainability. Therefore, co-ordinated global conservation strategies seem to be the only way forward.
Keywords: 330; Environmental Economics and Policy; Artenvielfalt; Entwicklung; Sozialprodukt; Umweltökonomik; Nachhaltige Entwicklung; Theorie; Environmental Kuznets Curve